Optimization of Phosphatidylcholine and Tween 80 Composition in the Formulation of Icariin Transfersome as a Transdermal Delivery System using Design-Expert - Setiyawan, Sukamto Jodi; Astuti, Ika Yuni; Hariyanti, Hariyanti (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Icariin is the main flavonoid of Epimedium sp. and has phosphodiesterase type-5 inhibitor (PDE5I) activity; however, its low water solubility and membrane permeability limit its oral bioavailability. The transferosome-based transdermal drug delivery system approach is considered promising because it can increase skin penetration and avoid the first-pass metabolism. This study aims to optimize the composition of phosphatidylcholine and Tween 80 in icariin-loaded transfersome vesicles to produce optimal physicochemical characteristics for transdermal applications. Method: Icariin transfersome was formulated using a thin-film hydration method with variations in phosphatidylcholine and Tween 80 concentrations. Optimization is performed using the Simplex Lattice Design (SLD) in Design Expert 13 software. The observed responses included particle size, polydispersity index (PDI), zeta potential, and Entrapment efficiency (EE%). The results of this study are the optimal formula of icariin transfersome, with a ratio of phosphatidylcholine and Tween 80 of 95%: 5%, resulting in ideal vesicle characteristics, namely a particle size of 106.15 nm, a zeta potential of -22.67 mV, a Polydispersity Index (PDI) of 0.37, and an Entrapment efficiency of 86.96%.